2022
DOI: 10.1186/s40621-022-00368-8
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of injuries in Japanese collegiate men’s basketball: 2013/2014 to 2019/2020

Abstract: Background Basketball is one of the most played sports in the world. However, only a few studies have examined the epidemiology of Japanese collegiate men’s basketball injuries. This study investigated the incidence of injury among Japanese collegiate men’s basketball from the 2013/2014 to the 2019/2020 seasons and identified unique patterns by comparing our data with the National Collegiate Athletic Association (NCAA) men’s basketball data. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Findings from individual studies revealed that 45%–94% 14,58,60 of ankle sprains resulted in a time loss of <7 days, 12%–18% 47,49 of ankle sprains resulted in a time loss of ≥10 days, while 2%–3% 59 of ankle sprains resulted in a time loss of >3 weeks in female and male basketball players. Injury history was not reported in six (40%) included studies 4,5,52,59,61,62 while another six studies reported that recurrent ankle sprains accounted for 19%–75% 13,14,47,49,57,58 of the ankle sprains documented.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from individual studies revealed that 45%–94% 14,58,60 of ankle sprains resulted in a time loss of <7 days, 12%–18% 47,49 of ankle sprains resulted in a time loss of ≥10 days, while 2%–3% 59 of ankle sprains resulted in a time loss of >3 weeks in female and male basketball players. Injury history was not reported in six (40%) included studies 4,5,52,59,61,62 while another six studies reported that recurrent ankle sprains accounted for 19%–75% 13,14,47,49,57,58 of the ankle sprains documented.…”
Section: Resultsmentioning
confidence: 99%
“…The mean score of the NHLBI Quality Assessment Scale was 70 ± 7% (range = 57%–86%, Table A2). Each of the 30 included studies in our meta‐analysis was of high quality with seven studies rated as excellent 13,14,46,62–65 and 23 studies rated as good 4,5,33,43–45,47–61,66,67 . All included studies clearly defined the objectives, participants examined, inclusion/exclusion criteria adopted, exposure of interest, timeframe adopted (years and/or period), independent variables involving repeated exposure assessments, and outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations